First‐Principles Molecular Dynamics Study on Ionic Structure and Transport Properties of NaCl‐MgCl2‐CaCl2 Ternary Molten Salt System. Issue 4 (5th February 2023) - Deng, Pan; Li, Liang; Jia, Yaoqiang; Jiang, Wenlong; Liu, Dachun; Chen, Xiumin; Kong, Lingxin
Abstract: The carbochlorination in molten salt is an effective method for titanium extraction form low‐grade titanium slag with a high calcium and magnesium content. However, in industrial practice, the fluidity of molten salt will gradually decrease with the increase of CaCl2 content. It is important to elucidate the influencing mechanism of CaCl2 content on the microstructure and diffusion properties of molten salt for the rational selection of a molten salt system and clean utilization of titanium slag. In this study, the densities of molten salt systems with different CaCl2 contents are measured according to the Archimedes principle. Then, using the first‐principles molecular dynamics (FPMD) method, the ionic structure and transport properties of NaCl‐MgCl2 ‐CaCl2 ternary molten salt systems under different CaCl2 contents are qualitatively and quantitatively described by determining the partial radial distribution functions (PRDF), coordination number (CN), angular distribution functions (ADF), and diffusion coefficient (DC). The results show that with the addition of CaCl2, Ca 2+ ion complexed with Cl − ion to form larger ionic clusters, which reduced the proportion of free Cl − ion and restricted the diffusion of Cl − ion. Abstract : The effect of CaCl2 on the NaCl‐MgCl2 ‐CaCl2 molten salt used for carbochlorination of low‐grade titanium slag is studied by first‐principles molecular dynamics. The existence of CaCl 6 4 − ${\rm{CaCl}}_{\rm{6}}^{{\rm{4}} - }$ ion cluster reduces the proportion of free Cl − ions and limits the mass transfer of Cl − ions. The content of CaCl2 should not exceed a maximum of 7.69 wt%.